Deadly drive (Minneapolis : Darby Creek, [, 2013)
When Rob Ramirez and Gabi Montoya skip out of school with two friends they find themselves in a deadly accident and as Rob sees his life forever changing, Gabi, the girl of his dreams blames him for what happened.